POULTRY FARMING START-UPS AS A GATEWAY FOR YOUTH EMPLOYMENT IN NIGERIA’S AGRO SECTOR - SADIQ MOHAMMED SANUSI; SINGH IP; AHMAD MM; SANI BS (Innovare Journal of Agricultural Sciences, 2025)
The agricultural sector in Nigeria remains a critical area for economic development, particularly in addressing youth unemployment. Poultry farming, an increasingly popular segment of the sector, offers a viable opportunity for youth entrepreneurship and job creation. This review explores the potential of poultry farming start-ups as a gateway to employment for young people in Nigeria; examining key factors such as accessibility, profitability, and the challenges encountered by young entrepreneurs. Through an analysis of recent literature and industry reports, this article investigates the theoretical and conceptual frameworks relevant to agro-entrepreneurship, discusses the results of various studies, and identifies best practices. The study concludes with recommendations on policies and support mechanisms to enhance youth participation in poultry farming as a means of achieving economic stability and growth.